Bacteriophages m13 and t4 increase the expression of anchorage-dependent survival pathway genes and down regulate androgen receptor expression in lncap prostate cell line - Sanmukh, Swapnil Ganesh [UNESP] (2021)
Wild-type or engineered bacteriophages have been reported as therapeutic agents in the treatment of several types of diseases, including cancer. They might be used either as naked phages or as carriers of antitumor molecules. Here, we evaluate the role of bacteriophages M13 and T4 in modulating the expression of genes related to cell adhesion, growth, and survival in the androgen-responsive LNCaP prostatic adenocarcinoma-derived epithelial cell line. LNCaP cells were exposed to either bacteriophage M13 or T4 at a concentration of 1 × 105 pfu/mL, 1 × 106 pfu/mL, and 1 × 107 pfu/mL for 24, 48, and 72 h. After exposure, cells were processed for general morphology, cell viability assay, and gene expression analyses. Neither M13 nor T4 exposure altered cellular morphology, but both decreased the MTT reduction capacity of LNCaP cells at different times of treatment. In addition, genes AKT, ITGA5, ITGB1, ITGB3, ITGB5, MAPK3, and PI3K were significantly up-regulated, whilst the genes AR, HSPB1, ITGAV, and PGC1A were down-regulated. Our results show that bacteriophage M13 and T4 interact with LNCaP cells and effectively promote gene expression changes related to anchorage-dependent survival and androgen signaling. In conclusion, phage therapy may increase the response of PCa treatment with PI3K/AKT pathway inhibitors.